2021
DOI: 10.3390/biomedicines9091267
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Cerebellar Cortex Injury in Albino Male Rats after MCAO: A Histological and Biochemical Study

Abstract: The present study focused on secondary injury following the middle cerebral artery (MCA) occlusion in rats not linked to the MCA’s feeding zone. This entity has been very rarely studied. Additionally, this study investigated the rates of expression of five fundamental angiogenic biomarkers called endoglin, vascular endothelial growth factors-A (VEGF-A), endothelin-1 (ET-1), 2granulocyte colony-stimulating factor (G-CSF), and angiopoietin-using the MCA occlusion (MCAO) model. The random allocation of twelve adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…In a study evaluating the morphological changes of brain cells after stroke, it was summarized that there were structural changes in the stem and axons of neurons in the ischemic area, vacuolization occurred in their plasms, and their nuclear structures were disrupted. They also noted the disintegration of Nissl granules, acidophilic cytoplasm, and red neuron formations disrupting protein structure (8,20). As a result of H&E staining in our samples, degenerated Purkinje cells, darkly stained cytoplasm, and spaces between nuclei and granular layer cells were visualized (Figure 2-B2).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In a study evaluating the morphological changes of brain cells after stroke, it was summarized that there were structural changes in the stem and axons of neurons in the ischemic area, vacuolization occurred in their plasms, and their nuclear structures were disrupted. They also noted the disintegration of Nissl granules, acidophilic cytoplasm, and red neuron formations disrupting protein structure (8,20). As a result of H&E staining in our samples, degenerated Purkinje cells, darkly stained cytoplasm, and spaces between nuclei and granular layer cells were visualized (Figure 2-B2).…”
Section: Discussionsupporting
confidence: 54%
“…Studies show that the pathological outcomes of experimental MCA-ischemia in rats and stroke in humans are similar (8).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo stroke models are now predominantly mice and rats, which is understandable given the lower costs of procurement and maintenance, as well as the ease of monitoring and tissue processing (Sommer, 2017). The intraluminal suture middle cerebral artery occlusion (MCAO) model, which does not need craniectomy, is the most commonly used experimental model for ischemic stroke in rats (Alrafiah, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The hypothalamus, which is a higher subcortical nerve center, is both a neuroendocrine regulatory center and a higher regulatory center of visceral activity. Hypothalamic injury causes pathological changes in some neurons, such as central chromatolysis, acute necrosis of neurons formed by neuronal nuclei consolidation and cytosolic shrinkage and deformation, and possibly the disintegration of myelin sheaths and axons and swelling of astrocytes [ 2 ]. These pathological changes can seriously affect neurological function.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the nerve injury caused by middle cerebral artery occlusion (MCAO) is not only limited to local infarction but can also cause secondary injury to distant regions, such as the hypothalamus, thalamus, substantia nigra, cerebellum, and spinal cord [ 1 , 2 ]. Studies have shown that transient middle cerebral artery occlusion (tMCAO) in rats can cause apoptosis and autophagy in cells in the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%